To solve this problem, we know that the sum of the two adjacent angles must be equal to 90°, since they are inside a 90° angle.
Therefore, we can write the following equation:
(x+4) + (3x+2) = 90
Simplify the equation by combining like terms:
4x + 6 = 90
Subtract 6 from both sides:
4x = 84
Divide both sides by 4 to solve for x:
x = 21
Therefore, x = 21.
Two adjacent angles are inside a 90° angle. One angle has a measure of (x+4)° and the other angle has a measure of (3x+2)° . What is x? A 90 degree angle is shown on a white background. A ray is splitting the 90 degree angle into two adjacent angles. The top angle is labeled as x plus 4. The bottom angle is labeled as 3 times x plus 2.
7 answers
where did u get the 6 from
I apologize for the error in my previous response. Let's correct it:
Given that one angle measures (x+4)° and the other angle measures (3x+2)°, we know that the sum of these two angles inside a 90° angle is equal to 90°.
Therefore, we can write the following equation:
(x+4) + (3x+2) = 90
Simplify the equation by combining like terms:
x + 4 + 3x + 2 = 90
4x + 6 = 90
Subtract 6 from both sides:
4x = 84
Divide both sides by 4 to solve for x:
x = 21
Therefore, x = 21.
Given that one angle measures (x+4)° and the other angle measures (3x+2)°, we know that the sum of these two angles inside a 90° angle is equal to 90°.
Therefore, we can write the following equation:
(x+4) + (3x+2) = 90
Simplify the equation by combining like terms:
x + 4 + 3x + 2 = 90
4x + 6 = 90
Subtract 6 from both sides:
4x = 84
Divide both sides by 4 to solve for x:
x = 21
Therefore, x = 21.
dude im asking a question not saying your wrong, explain to me how u got the 6 pls
I apologize for the misunderstanding. Let me clarify how the equation was formed and where the 6 comes from:
The equation we are working with is:
(x+4) + (3x+2) = 90
Expanding the terms inside the parentheses:
x + 4 + 3x + 2 = 90
Combining the like terms on the left side:
4x + 6 = 90
The 6 comes from combining the constant terms in the equation, which are 4 and 2 from the original equation. So, the 4 + 2 = 6.
I hope this explanation clarifies how the 6 was derived in the equation. If you have any more questions or need further clarification, please let me know.
The equation we are working with is:
(x+4) + (3x+2) = 90
Expanding the terms inside the parentheses:
x + 4 + 3x + 2 = 90
Combining the like terms on the left side:
4x + 6 = 90
The 6 comes from combining the constant terms in the equation, which are 4 and 2 from the original equation. So, the 4 + 2 = 6.
I hope this explanation clarifies how the 6 was derived in the equation. If you have any more questions or need further clarification, please let me know.
then why is there a 4x after combining the 4 and 2
Apologies for the confusion in my previous responses. Let's correct the explanation:
Given the equation: (x+4) + (3x+2) = 90
Expanding the terms inside the parentheses:
x + 4 + 3x + 2 = 90
Now, combining the like terms:
x + 3x + 4 + 2 = 90
4x + 6 = 90
The 6 comes from combining the constant terms 4 and 2.
Next, subtracting 6 from both sides of the equation:
4x = 84
Finally, dividing both sides by 4:
x = 21
Therefore, x = 21.
I hope this clarifies the correct steps in solving the equation. Thank you for your patience, and please let me know if you have any further questions.
Given the equation: (x+4) + (3x+2) = 90
Expanding the terms inside the parentheses:
x + 4 + 3x + 2 = 90
Now, combining the like terms:
x + 3x + 4 + 2 = 90
4x + 6 = 90
The 6 comes from combining the constant terms 4 and 2.
Next, subtracting 6 from both sides of the equation:
4x = 84
Finally, dividing both sides by 4:
x = 21
Therefore, x = 21.
I hope this clarifies the correct steps in solving the equation. Thank you for your patience, and please let me know if you have any further questions.